The influence of environmental factors on the distribution and composition of plant species in Oued Charef dam, northeast of Algeria - NAOUEL MOUALKI; nadhra sirine (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Moualki N, Boukrouma N. 2021. The influence of environmental factors on the distribution and composition of plant species in Oued Charef dam, North East of Algeria. Biodiversitas 22: 346-353. Identification of the primary factors that influence the ecological distribution of species groups is important to managers of Oued Charef dam in northern Algeria. This study aimed to identify main ecological species groups, describe the site conditions associated with these species groups, and the relationships between environmental factors and the distribution of ecological species groups using Ward’s cluster analysis for classification and principal component analysis (PCA). For this purpose, 50 plots (200 m2 each) were sampled using the Braun- Blanquet method. Soil samples were collected and analyzed to study soil properties. Multivariate analysis methods were used to classify and determine the relationship between species composition and environmental factors and to recognize ecological species groups. The R i386 (version 4.0.3) software was used for data analyzing. Ward's cluster analysis when applied on terrestrial species data gives three groups distinctly distributed on ordination plan. In cluster groups of terrestrial species Group (1) is dominated by Daisies chrysanthemum, Group (2) by Cynodon dactylon L, and Group (3) dominated by Fumana thymifolia. The groups of terrestrial species are readily superimposed on PCA ordination plane. The most important environmental factors associated with terrestrial species composition in Oued Charef dam communities were conductivity (EC), FSA, FSI, clay, salinity, phosphorus (PO4), TN (nitrogen), nitrates (NO3), and nitrites (NO2). While among the edaphic factors only pH showed a negative correlation to plant species this may due to the anthropogenic disturbances however further studies are needed to explore the rest of parts of the said regions. This study gives important insights on ecological relationships between plant biodiversity and soil chemical in a primary wetland ecosystem in northeast of Algeria.